Aplicação de revestimento à base de quitosana incorporado com o extrato do resíduo de cebola (allium cepa l.) Em carne bovina - Silva, Maria Raquel Lopes (Universidade Federal Rural do Semi-Árido, 2019)
Edible coatings and films prepared from natural sources find special attention, having importance for increasing the shelf life of foods of animal origin. The objective of this work was to characterize the effect of the application of edible coatings to the chitosan base with the incorporation of the extract of the onion residue (Allium cepa L.) to maintain the quality of beef under refrigeration (4 ± 1 ° C, for 8 days). Analyzes of film characterization, physical-chemical and microbiological analyzes were carried out on meat samples. It can be verified that the coatings had a homogeneous surface, dense, without cracks and without pores. For tensile strength at rupture there was no statistical difference (P> 0,05). Regarding the rate of deformation at the point of rupture, these presented a statistical difference (P <0,05). The addition of the extract of the onion residue in the coatings influenced the parameters L * and a *, presenting a statistical difference (P <0,05). As regards the transmission of ultraviolet light, the samples decreased the absorption of light with the increase of the amount of the extract. It was observed that the extract application was effective in reducing lipid oxidation (evaluated by TBARS). For thermotolerant coliform microorganisms, these values remained stable. No microbial growth was found for Salmonella. Regarding the aerobic mesophilic bacteria, growth was observed during all sample days and in all treatments, with a statistical difference (p <0,05). In the quantification of Staphylococcus ssp. growth of microorganisms was also observed. In this way, the chitosan film with the addition of the extract of the onion residue proved to be a viable alternative as a natural preservative, maintaining the shelf life of the beef
Keywords: Cobertura; Conservante; Vida de Prateleira; Roof; Preservative; Shelf Life; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL